Pengaruh Sosial Media Marketing Dan Citra Merek Terhadap Keputusan Pembelian Mie Gacoan Situbondo - Ainul Yaqin; Ahmad Hafas Rasyidi; Dassucik Dassucik (Universitas Hamzanwadi, 2026)
The rapid development of digital technology has prompted businesses to adjust their marketing strategies by leveraging social media, which has become an effective tool for promotion, consumer interaction, and brand image building Mie Gacoan, as a culinary brand, actively utilizes social media to attract consumers’ attention, particularly among the younger generation. This study aims to analyze the influence of social media marketing and brand image on the purchase decisions of Mie Gacoan consumers in Situbondo. The research employed a quantitative survey approach, involving 102 consumers selected through accidental sampling. Data were collected using a five-point Likert scale questionnaire and analyzed through multiple linear regression. The results indicate that both social media marketing and brand image have a positive and significant effect on purchase decisions. Partially, brand image contributes more than social media marketing, while simultaneously, the two variables explain 61.9% of the variation in purchase decisions. These findings underscore that integrating digital marketing strategies through social media with brand image enhancement can improve the effectiveness of consumer purchase decisions. The study provides practical insights for developing digital marketing strategies in the culinary industry and offers a foundation for future research with an expanded scope of variables and geographical coverage.